Penguatan Literasi Bahasa Indonesia Bagi Remaja melalui Program Pojok Baca di Sekolah - Suryanti, Suryanti (Yayasan Literasi Sains Indonesia, 2025)
This community service program aims to strengthen Indonesian language literacy among teenagers by optimizing the Reading Corner in schools. Good literacy skills are essential for improving language comprehension and proficiency; however, reading interest among teenagers remains relatively low. Therefore, this program is designed to create a comfortable, engaging, and interactive reading environment by providing reading materials that align with students' interests and needs. Activities include reading assistance, book discussions, creative writing workshops, and literacy competitions to enhance students' enthusiasm for the Indonesian language. Additionally, the program involves teachers as facilitators to instill sustainable reading habits. Through this initiative, students are expected not only to develop a greater interest in reading but also to enhance their ability to comprehend, analyze, and express ideas effectively in writing. The success of this program is measured by the increased student participation in literacy activities and their ability to process and produce Indonesian-language texts. Thus, the school Reading Corner can serve as an effective tool for fostering a literacy culture and sustainably improving teenagers' language proficiency.